Eksistensialisme Rafathar dalam Praktik Sharenting pada Media Sosial Raffi Ahmad dan Nagita Slavina - Ketut Ajeng Sespiani (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Sharenting has become popular activities done by artists and celebrities. Sharenting is categorized as the activity of sharing photos or videos of children on social media, where the child's personal information can be accessed by the public. Through descriptive qualitative approach and observation on Raffi Ahmad and Nagita Slavina’s Instagram account, this paper aims to point out Rafatar’s existence emphasising on sharenting practices. The results showed that the sharenting practices carried out by the two couples ignored the essence of Rafathar's right to privacy by not maintaining Rafathar's subjectivity and prioritizing financial gain. The form response of criticism or public support for the practice of sharenting, is only a form of objectivity by other individuals.